Prevalence of Methicillin Resistant Staphylococcus aureus in Raw Goat Milks from Selected Farms in Terengganu, Malaysia - M. H. Chai; T. A. M. Faiq; S. M. Z. Ariffin; Z. Suhaili; M. Z. Sukiman; M. F. Ghazali (Faculty of Animal Science, Bogor Agricultural University, 2020)
The emergence of antimicrobial drug resistant bacteria has been a concern worldwide. One of bacteria that has been reported to develop resistance is Methicillin Resistant Staphylococcus aureus (MRSA). Recent studies showed that Livestock Associated MRSA (LA-MRSA) was found in domestic food animals and their handlers. The aim of this study was to investigate the prevalence of MRSA in goat milk of goat farms located in Terengganu. A total of 664 udder milks were taken from 332 goats at 40 selected farms within Terengganu state. Then, screening of bacteria and isolation of suspected S. aureus isolates in the milk samples was done using selective agar, Gram staining and biochemical tests. The identity of the bacteria isolated was further confirmed using PCR where specific designed primers were used to detect the presence of nuc gene of S. aureus (278bp) and mecA gene (533bp) of MRSA. Both S. aureus and MRSA isolates were also tested for their susceptibilities toward the antimicrobial drugs. Fifty milk samples were found to contain S. aureus and one of the S. aureus isolates were MRSA. The bacteria isolates were found to have higher tendency to be resistance toward Penicillin (26.0%) and Oxacillin (12.0%). This study provides useful data on the current status of MRSA prevalence in small ruminant’s milk, which can be used to prevent transmission of LA-MRSA to human and other animals.